Modeling of cold mix asphalt evolutive behaviour based on nonlinear viscoelastic spectral decomposition. (10th June 2018) - Lambert, Marion; Piau, Jean-Michel; Gaudefroy, Vincent; Millien, Anne; Dubois, Frédéric; Petit, Christophe; Chaignon, François
Highlights: Develop an evolutive constitutive model for cold mixes treated with bitumen emulsion. Develop an oedometric test to study the cold mix asphalt evolutive behaviour. Spectral merging between nonlinear elasticity and viscoelasticity. Abstract: Given a political context in which energy and environmental stakes have become increasingly dominant, road engineering practices have favoured saving energy and protecting the environment. Among these practices, the use of cold mixes treated with bitumen emulsion has proven to be a suitable technique. Cold mix design, as well as the design of pavements including cold mix asphalt (CMA) layers, is highly empirical and based on local skills and tend to limit the development of this environmentally-friendly pavement technique. In the case of CMA, no mechanical behaviour law has been established to take into account its evolutive behaviour. The paper is set in three parts. The CMA model is presented in Part I. The second part of the paper illustrates the numerical response of the model on a compressive sinusoidal load. The last part presents some first simulations of the cyclic oedometer laboratory tests. By comparing then to the numerical simulations, they show the relevance of the model to account for the CMA behaviour.